SOCIAL-EMOTIONAL LEARNING (SEL) IN PRIMARY SCHOOLS AND ITS IMPACT ON ACADEMIC SUCCESS - Navro‘zova Nasima Sardor qizi (Bright Mind Publishing, 2026)
This article analyzes the theoretical foundations of the formation of Social and Emotional Learning (SEL) competencies in primary school students and its influence on academic success. The study highlights the impact of SEL components self-awareness, self-regulation, social awareness, relationship building, and responsible decision-making skills on students' reading, mathematics, and overall learning outcomes. It also substantiates the mechanisms for integrating SEL into primary education, pedagogical conditions and expected results. The results of the study indicate that the SEL approach is an important factor in ensuring students' psychological well-being and social adaptation while enhancing their academic performance.
Keywords: Social-emotional learning, SEL, primary school, academic success, emotional intelligence, competency approach, educational effectiveness.